Estimation of sustainable development: Germination on institutional level - Grybaitė, Virginija; Tvaronavičienė, Manuela (Journal of Business Economics and Management, 2008)
The aim of the paper is to investigate approaches to measurement of sustainable development adopted by international organizations, or institutions. Organizations for sustainable development were founded to review progress at the international, regional and national levels in the implementation of sustainable development policy, to take part in legislative process, to control balance between economic development, social development, and environmental development. Valid systems and classifications of sustainable development are being juxtaposed, specific features, advantages and disadvantages revealed. The question, if the systems of indicators provided by considered institutions are applicable for practical analytical purposes, is being raised. First published online: 14 Oct 2010